(untitled) (UNIZIK Journal of Marketing, 2024)
This study examined social media marketing and purchase decision of Smartphone users in Lagos State, Nigeria, with a focus on Samsung and Apple iPhone. Quantitative research method and descriptive survey design were adopted. The population of study consists of all users of Samsung and Apple iPhones in Lagos, whose population size is undefined. The one hundred sample size considered for the study was determined via Fisher’s formula for undefined population, and participants were sampled through an online survey; out of which 94 responses was retrieved. Purposive technique was employed in drawing members of the sample and collected data was analyzed with descriptive and inferential statistics. The study found and concluded that there is significant relationship ship between Facebook advertisements and consumer choices of smart phones; that there is significant relationship between Instagram postings and brand choice of Smartphone users; that there is no significant relationship between celebrity endorsements of Smartphone on social media and consumer’s brand choices; and that a significant relationship exists between social media marketing and purchase decision of Smartphone Users in Lagos Nigeria. Against this background, the study recommends that Management of Samsung and Apple iPhones among other Smartphones in Lagos Nigeria should leveraged on pushing out positive e-Word of Mouth on social media to promote sales and brand performance. Additionally, marketers of smart phones should give incentives to encourage consumers to share/post their positive experiences; as well as recommend their brands on social media.